Pengukuran Moderasi Beragama pada Mahasiswa Universitas Nahdlatul Ulama Blitar di Era Milenial - Nur Safaat, Ahmad Wafi; Rosyadi, Zainal; Maula, Silvia Rohmatul; Kasanah, Siti Uswatun (Universitas Nahdlatul Ulama Blitar, 2024)
The aim of this research is to measure the description and implementation of various moderation among UNU Blitar students in. The negative impact of the easy dissemination of information through social media requires prevention, students know the negative impact of the development of science and technology so that students have morals that are not extreme through religious moderation. Religious moderation is interpreted as an attitude, idea, or thought that tries to be in a middle position between different problems, so that it does not take sides or harm those that are excessive or extreme right or extreme left. The results of the research show that UNU Blitar students show a fairly strong attitude of religious moderation on the four indicators measured. This shows that they tend to have moderate and open views on religion, supporting tolerance, non-violence, commitment, and understanding local culture.